Evaluation of calcium and folic acid supplementation in prenatal care in São Paulo - Silva, Camila Atallah Pontes da; Silva, Carolina Atallah Pontes da; Atallah, Álvaro Nagib; Sass, Nelson; Mendes, Eliane Terezinha Rocha; Peixoto, Sérgio (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Preeclampsia and neural tube defects can be prevented during pregnancy. Today, there is level I evidence showing that calcium supplementation during pregnancy may prevent preeclampsia and that use of folic acid may prevent neural tube defects. The aim here was to evaluate the proportion of patients undergoing prenatal follow-up who had received a prescription for calcium and/or folic acid supplementation, and their adherence to the use of these two substances. DESIGN AND SETTING: Cross-sectional study at two hospitals in the Greater São Paulo region, Brazil (Faculdade de Medicina da Fundação ABC, Santo André, and “Dr. Mário de Moraes Altenfelder Silva” Municipal Teaching and Maternity Hospital, Vila Nova Cachoeirinha). METHODS: Early primigravidae, late primigravidae and pregnant women with chronic hypertension, diabetes mellitus or kidney disease who had already had their first prenatal consultation were included. RESULTS: Out of 250 pregnant women interviewed, 10.40% had received a prescription for calcium supplementation and 80.76% of them reported taking it in tablet form. Regarding folic acid, 48% of the women said that they had received a prescription for this and 64.16% reported that they had started to use it during the periconceptional period. CONCLUSIONS: Calcium supplementation and periconceptional use of folic acid seem not to be prescribed routinely by physicians. This should motivate the implementation of educational programs for obstetricians on the use of interventions based on the best available evidence.